Pengaruh Sistem Akuntansi Manajemen, Sistem Pengendalian Manajemen, Motivasi dan Kmitmen Organisasi Terhadap Kinerja Manajerial - Agustina Dwita Sari; Sri Luayyi; Puji Rahayu (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to determine the influence of management accounting systems, management control systems, motivation and organizational commitment on the managerial performance of PT Wonojati Wijoyo. This case study was conducted at PT Wonojati Wijoyo in 2019-2021 which consists of variables (X) including: management accounting system, management control system, motivation, organizational commitment, variable (Y) managerial performance. The sampling technique uses a saturated sampling technique. The results of this research show that H1 the management accounting system has a significant effect on managerial performance, while H2 the management control system has a significant effect on managerial performance, H3 motivation has a significant effect on managerial performance, H4 organizational commitment has no effect on managerial performance. Based on the four equations, it proves that managerial performance has a high influence on the company.